Pengaruh Penyesuaian Sosial, Dukungan Sosial dan Keterampilan Sosial Sebagai Moderator Pembentukan Perilaku Sosial Siswa di Sekolah - Yunita Yunita (Indonesian Journal of Social Science Education (IJSSE), 2023)
Students' social problems at school often arise and have an impact on students' social behavior, this needs to be an important concern for teachers to know. The purpose of this study was to determine the effect of social adjustment, social support and social skills as a moderator of the formation of students' social behavior at school. The research method used ex post facto designs. This research was conducted at SMA Kartika I-2 Medan, the population of this research was class XI students, the research sample was 75 students. Data collection uses a scale of social adjustment, social support, and social skills. Data analysis using multiple linear regression analysis. The findings show that there is an influence (sig.<0.05) between social adjustment, social support, and social skills variables on social behavior variables (R=0.860, R2=0.887, F=179.853, Sig.=0.000). The results showed that there is an influence of social adjustment, social support, and social skills as a moderator of the formation of students' social behavior. The results of this study contribute as a novelty for teachers, academics and observers in the fields of education, psychology and social affairs.